In vitro susceptibility of Citrobacter species to various antimicrobial agents. - Samonis, G (1987)
The in vitro activities of 16 antimicrobial agents against 14 clinical isolates of Citrobacter diversus and 27 isolates of Citrobacter freundii were studied. C. freundii isolates were more resistant, being susceptible only to amikacin, netilmicin, gentamicin, imipenem, ciprofloxacin, and enoxacin. C. diversus isolates were susceptible to many more of the agents tested.